ADDRESSING WRONGFUL CONVICTIONS IN CROATIA: A FOCUS ON GENETIC PRIVACY IN CRIMINAL PROCEEDINGS (EU and comparative law issues and challenges series (ECLIC), 2024)
This paper addresses the intricate challenges of genetic privacy in criminal investigations, particularly within the Croatian context. Conducted by the Croatian Innocence Project, workshops emphasized key issues like DNA material handling, databasing, and the need for legal framework improvements and further research on this topic. The findings of several cases of the ECtHR underscored the risk of miscarriages of justice when genetic privacy is neglected. The paper explores genetic privacy through three elements: treatment of genetic materials, forensic errors, and DNA databasing. Analyzing European Court of Human Rights cases and trends in the U.K., U.S., and E.U., it provides insights to enhance Croatia's legal framework. The study aims to demonstrate the delicate balance between genetic privacy in handling genetic data and effective criminal prosecutions.